2020
DOI: 10.5213/inj.2040058.029
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Neurogenic Bladder Dysfunction in Rodent Models: A Systematic Review

Abstract: Purpose: Neurogenic bladder dysfunction (NGB) has an impact on the quality of life, which made it an important research subject in preclinical studies. The present review investigates the effect of stem cell (SC) therapy on bladder functional recovery after the onset of spinal cord injury (SCI), multiple sclerosis (MS), Parkinson disease (PD), and stroke in rodent models.Methods: All experiments evaluated the regenerative potential of SC on the management of NGB in rodent models up to June 2019, were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) were also found to inhibit fibrosis via the TGF-beta 1 signaling pathway. [37] Adipose tissue-derived mesenchymal stem cells (AT-MSCs) were studied for smooth muscle cell (SMC) differentiation on scaffolds and tissue culture polystyrene (TCPS) surfaces. This biofunctional scaffold aims to repair and regenerate bladder tissues and promote the restoration of NB (NGB) function through the multidirectional differentiation potential of stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs) were also found to inhibit fibrosis via the TGF-beta 1 signaling pathway. [37] Adipose tissue-derived mesenchymal stem cells (AT-MSCs) were studied for smooth muscle cell (SMC) differentiation on scaffolds and tissue culture polystyrene (TCPS) surfaces. This biofunctional scaffold aims to repair and regenerate bladder tissues and promote the restoration of NB (NGB) function through the multidirectional differentiation potential of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) were also found to inhibit fibrosis via the TGF-beta 1 signaling pathway. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to a systematic review on stem cell therapy for NBD in rodent models published in 2020, out of 20 studies eligible for review, 15 were conducted on SCI, 2 were conducted on PD, 2 were conducted on stroke, and 1 was conducted on MS [ 44 ]. The review concluded that the common SC sources used for therapeutical purposes were neural progenitor cells, bone marrow mesenchymal SCs, human amniotic fluid SCs, and human umbilical cord blood SCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the selectivity or priority of the molecules that actually pass through the gap junctions has not been clarified. Cell–cell communication and signaling are regulated by the exchange of small soluble molecules between cells through gap junction channels 13 . This exchange between stem cells and vascular endothelial cells via gap junctions is important for both HSCs and MSCs in cell therapies after stroke 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…With the recent development of stem cell research, cell therapy has been studied as a new therapeutic strategy for various diseases [1][2][3][4][5][6][7][8][9][10][11][12][13] . Hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs) are major cell sources in cell-based therapies.…”
Section: Introductionmentioning
confidence: 99%